1990
DOI: 10.1161/01.str.21.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac evaluation of the patient with stroke.

Abstract: Coronary artery disease and ischemic cerebrovascular disease are leading causes of morbidity and mortality in the United States. Coronary artery disease often coexists with asymptomatic carotid artery atherosclerosis, transient ischemic attacks, or ischemic stroke. Numerous studies have shown that mortality from all forms of ischemic cerebrovascular disease is primarily due to coronary artery disease. Thus, there is increasing interest in identifying coronary artery disease in patients with cerebrovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 103 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…As also found in the present study, preference for the carotid circulation in embolic strokes as well as leftsided predominance have been reported: 78%-90% of all cardiogenic emboli to the brain lodge in the middle cerebral artery [7,15,29]. In a clinicopathological analysis of 142 proven cases of cerebral embolism, Masuda et al [22] found the middle cerebral artery territory affected in 113 cases, and the area supplied by the verebrobasilar arteries in 37 cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As also found in the present study, preference for the carotid circulation in embolic strokes as well as leftsided predominance have been reported: 78%-90% of all cardiogenic emboli to the brain lodge in the middle cerebral artery [7,15,29]. In a clinicopathological analysis of 142 proven cases of cerebral embolism, Masuda et al [22] found the middle cerebral artery territory affected in 113 cases, and the area supplied by the verebrobasilar arteries in 37 cases.…”
Section: Discussionsupporting
confidence: 82%
“…With emphasis on coronary heart disease, there is increasing evidence that the prognosis of patients with cerebrovascular disease is critically influenced by cardiac disorders [12,29].…”
Section: ]mentioning
confidence: 99%
“…Coronary artery disease was more extensive (P=.O12), and a higher percentage of these patients had a history of peripheral C erebral embolism from cardiac disease and cerebrovascular arterial disease are common causes of embolic neurological events in a significant number of patients. 1 Cardiac emboli can arise from thrombi in the left ventricle, left atrium, or left atrial appendage or paradoxically from the right atrium through an atrial septal defect or patent foramen ovale.…”
mentioning
confidence: 99%
“…Among the possible causes of cerebral ischemia in young adults mitral valve prolapse appears to be one of the commonest [8, [24][25][26][27], Nevertheless, if restrictive echocardiographic criteria are adopted [15,28], mitral valve prolapse is less frequently identified [3. 5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional echocardiography is the main noninvasive imaging technique for detecting occult cardiac diseases, and identifying the anatomical features of the embologenic lesions [ 10], Nevertheless, the indications of two-dimensional echocardiography in patients with re cent cerebral ischemia are still debated [11][12][13][14][15].…”
mentioning
confidence: 99%